Inverse Binomial Sum

Calculus Level 2

n = 3 1 ( n 3 ) = 1 ( 3 3 ) + 1 ( 4 3 ) + 1 ( 5 3 ) + 1 ( 6 3 ) + = ? \displaystyle \sum_{n=3}^{\infty} \dfrac{1}{\binom{n}{3}} = \dfrac{1}{\binom{3}{3}} + \dfrac{1}{\binom{4}{3}} + \dfrac{1}{\binom{5}{3}} + \dfrac{1}{\binom{6}{3}} + \cdots = \, ?


The answer is 1.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Feb 10, 2017

Relevant wiki: Partial Fractions - Repeated Factors

S = n = 3 1 ( n 3 ) = n = 3 3 × 2 n ( n 1 ) ( n 2 ) = n = 1 6 n ( n + 1 ) ( n + 2 ) = 6 2 n = 1 ( 1 n 2 n + 1 + 1 n + 2 ) = 3 n = 1 ( 1 n 1 n + 1 1 n + 1 + 1 n + 2 ) = 3 ( 1 1 2 ) = 3 2 = 1.5 \begin{aligned} S & = \sum_{n=3}^\infty \frac 1{n \choose 3} \\ & = \sum_{n=3}^\infty \frac {3\times 2}{n(n-1)(n-2)} \\ & = \sum_{\color{#3D99F6}n=1}^\infty \frac {6}{\color{#3D99F6}n(n+1)(n+2)} \\ & = \frac 62 \sum_{n=1}^\infty \left(\frac 1n - \frac 2{n+1} + \frac 1{n+2} \right) \\ & = 3 \sum_{n=1}^\infty \left(\frac 1n - \frac 1{n+1} - \frac 1{n+1} + \frac 1{n+2} \right) \\ & = 3 \left( 1 - \frac 12 \right) = \frac 32 = \boxed{1.5} \end{aligned}

Sir, i try to solve in the same way but i got halted by 3rd step where i tried breaking them without using partial fraction. Can you tell me any such trick to break without using fraction? :)

Naren Bhandari - 3 years, 8 months ago

Log in to reply

I broke it without using partial fractions:

6 1 ( n 1 ) n ( n 2 ) 6\sum \dfrac{1}{(n-1)n(n-2)}

3 1 n 1 . n ( n 2 ) n ( n 2 ) 3 \sum \dfrac{1}{n-1} . \dfrac{n - (n - 2)}{n(n-2)}

3 1 n 1 ( 1 n 2 1 n ) 3 \sum \dfrac{1}{n-1} \left( \dfrac{1}{n-2} - \dfrac{1}{n} \right)

I also tried to group n with n- 1 and n - 1 with n - 2 but only this one telescopes.

Shubhrajit Sadhukhan - 4 months, 3 weeks ago

Relevant wiki: Telescoping Series - Sum

n = 3 1 ( n 3 ) = 1 ( 3 3 ) + 1 ( 4 3 ) + 1 ( 5 3 ) + 1 ( 6 3 ) + = 6 ( 1 1 2 3 + 1 2 3 4 + 1 3 4 5 + 1 4 5 6 + ) \displaystyle \sum_{n=3}^{\infty} \dfrac{1}{\binom{n}{3}} = \dfrac{1}{\binom{3}{3}} + \dfrac{1}{\binom{4}{3}} + \dfrac{1}{\binom{5}{3}} + \dfrac{1}{\binom{6}{3}} + \cdots = 6(\dfrac{1}{1\cdot 2\cdot 3} + \dfrac{1}{2\cdot 3\cdot 4} + \dfrac{1}{3\cdot 4\cdot 5} + \dfrac{1}{4\cdot 5\cdot 6} + \cdots)

Observe that 1 1 2 1 2 3 = 3 1 1 2 3 = 2 1 2 3 \dfrac{1}{1\cdot 2} - \dfrac{1}{2\cdot 3} = \dfrac{3-1}{1\cdot 2\cdot 3} = \dfrac{2}{1\cdot 2\cdot 3} , and it will be similar to other fractions:

6 ( 1 1 2 3 + 1 2 3 4 + 1 3 4 5 + 1 4 5 6 + ) = 6 2 ( 1 1 2 1 2 3 + 1 2 3 1 3 4 + 1 3 4 1 4 5 + ) 6(\dfrac{1}{1\cdot 2\cdot 3} + \dfrac{1}{2\cdot 3\cdot 4} + \dfrac{1}{3\cdot 4\cdot 5} + \dfrac{1}{4\cdot 5\cdot 6} + \cdots) = \dfrac{6}{2}(\dfrac{1}{1\cdot 2} - \dfrac{1}{2\cdot 3}+\dfrac{1}{2\cdot 3} - \dfrac{1}{3\cdot 4} +\dfrac{1}{3\cdot 4} - \dfrac{1}{4\cdot 5} + \cdots)

All the latter terms are cancelled out, and we are left with:

3 ( 1 2 ) = 1.5 3(\dfrac{1}{2}) = \boxed{1.5}

Did the same

I Gede Arya Raditya Parameswara - 4 years, 3 months ago

Wrong way bt still got ryt ans

ritik raj - 3 years ago

U checked only 1 term ,what about next term....

ritik raj - 3 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...